2014
DOI: 10.1371/journal.pone.0104164
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Post-Transplant Acute Kidney Injury: Assessment of Whole-Genome mRNA and MiRNA Profiles

Abstract: Acute kidney injury (AKI) affects roughly 25% of all recipients of deceased donor organs. The prevention of post-transplant AKI is still an unmet clinical need. We prospectively collected zero-hour, indication as well as protocol kidney biopsies from 166 allografts between 2011 and 2013. In this cohort eight cases with AKI and ten matched allografts without pathology serving as control group were identified with a follow-up biopsy within the first twelve days after engraftment. For this set the zero-hour and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 49 publications
2
50
0
Order By: Relevance
“…These differentially expressed miRNAs include miR-638, miR-663, miR198, miR-155, and miR-146a (91,141). Similarly, acute allograft rejection, a frequent complication of renal transplantation, is associated with alterations in miRNA expression (4,84,95,143,160). Global miRNA profiling of human hypertensive nephrosclerosis biopsies also revealed a number of differentially expressed miRNAs, including miR-200a, miR-200b, miR-141, miR-429, and miR-192 (150).…”
Section: Other Renal Diseases and Conditionsmentioning
confidence: 98%
See 1 more Smart Citation
“…These differentially expressed miRNAs include miR-638, miR-663, miR198, miR-155, and miR-146a (91,141). Similarly, acute allograft rejection, a frequent complication of renal transplantation, is associated with alterations in miRNA expression (4,84,95,143,160). Global miRNA profiling of human hypertensive nephrosclerosis biopsies also revealed a number of differentially expressed miRNAs, including miR-200a, miR-200b, miR-141, miR-429, and miR-192 (150).…”
Section: Other Renal Diseases and Conditionsmentioning
confidence: 98%
“…Although, extensive human studies are still required, initial steps have been taken to demonstrate the potential utility of miRNAs, especially in the urine, for assessing AKI. Multiple studies (90,96,104,113,124,155,159,160) in humans and animal models have identified specific miRNAs as potential diagnostic markers for the early detection of AKI. Such approaches would be of tremendous clinical value to prevent progression from AKI to renal failure.…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…Analysis of human renal allograft biopsies demonstrated that increased expression of miR-182 is associated with both antibody-mediated rejection and acute kidney injury 14,29 . Our studies, and others, have demonstrated FOXO1 as a target of miR-182 and indeed FOXO1 was significantly increased in miR-182 −/− recipients of cardiac allografts treated with CTLA4-Ig supporting a role for FOXO1 in graft survival 8,13,30 .…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are involved in the regulation of angiogenesis and apoptosis through TGF-b, endothelin, vascular endothelial growth factor, and PDGF signaling (19). Upregulation of miR-182-5p, miR-21-3p, and miR-146a have been reported (20,21). The overexpression of miR-146a probably represents a compensatory mechanism because in vitro experiments identified the role of miR-146a as a negative regulator of inflammation in tubular cells by downregulation of the NFkB/C-X-C motive chemokine ligand 8 pathway (21).…”
Section: Kidney Transplantationmentioning
confidence: 99%